PENINGKATAN EFISIENSI BIAYA DAN MUTU RENGGINANG MELALUI PENERAPAN KOMPOR BERBAHAN BAKAR JELANTAH DAN PENGELOLAAN LIMBAH AIR CUCIAN BERAS - Fatimah, Ai Tusi; Setiawan, Tia; Amalia, Lidya Nur (Jurnal Abdi Insani, 2025)
High energy costs and the challenge of managing used cooking oil waste are major obstacles for the Rengginang Hj UAS Home Industry in Ciamis, resulting in low profit margins and sub-optimal product quality. Therefore, this activity aims to transform the partner IRT into an efficient, competitive, and environmentally sustainable Micro, Small, and Medium Enterprise (MSME). The method employed was the multidisciplinary STEAM-H approach through intensive training, implementation of Appropriate Technology in the form of a Used Cooking Oil Stove and a De-oiling Machine, as well as the application of a Zero-Waste system (conversion of rice washing wastewater into Liquid Organic Fertilizer/POC). Evaluation results showed significant success, with partner competency increasing to a Normalized Gain (N-Gain) value of 0.72 (High Category) and achieving 100% mastery of practical skills. Economically, the program exceeded targets by reducing fuel costs by up to 65% and increasing oil separation efficiency by 100%. The technology adoption rate fell into the Very High Category (score: 4.64). However, the Zero-Waste aspect (raw material independence) was only 20% achieved and requires further assistance. In conclusion, the program was effective in substantially transforming the partner's operational efficiency and product quality.